Type-3 Fuzzy System-Based Intelligent Control Approaches and Applications - Turki Y. Abdalla; AbdulKareem Y. Abdalla; Adala M. Chyaid (Advances in Fuzzy Systems)
Type-3 fuzzy logic has been recently used in many control methods. The type-3 fuzzy controller enhances the handling of uncertainty and improves robustness by integrating fuzzy sets with fuzzy membership functions. The latest approaches using type-3 fuzzy logic in the field of control are studied and evaluated. An overview of developments in control methods based on type-3 fuzzy logic is also provided. It is shown that type-3 fuzzy system has many advantages compared to type-1 and type-2 fuzzy. The advantages and challenges of using type-3 fuzzy logic are identified and discussed. The studies are classified according to the type of control approach, as well as by the type of control applications. Finally, the main achievements, open challenges, and future directions and impacts are identified, to provide important guidance for interested researchers.